A Graphical User Interface (GUI) Approach Of Voltage Instability Analysis Based On P-V And Q-V Curves In Radial Power System Networks - Sulaiman, Marizan; Bujal, Noor Ropidah; Omar, Rosli (BRIS Journal Of Advanced Science & Technology (BRISJAST), 2015)
-